Salt-Tolerant Synechococcus elongatus UTEX 2973 Obtained via Engineering of Heterologous Synthesis of Compatible Solute Glucosylglycerol - Cui, Jinyu; Sun, Tao; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2021)
A recently isolated cyanobacterium Synechococcus elongatus UTEX 2973 (Syn2973) is characteristic of faster growth rate, more tolerance to high-temperature and high-light, making it a good candidate chassis for autotrophic photosynthetic microbial cell factory. However, Syn2973 is sensitive to salt stress, raising the urgency to improve the salt tolerance of Syn2973 for future biotechnological application. Glucosylglycerol as a compatible solute plays an important role in resisting salt stress in moderate and marine halotolerant cyanobacteria. In this study, salt tolerance of Syn2973 was successfully improved by introducing the GG biosynthetic pathway (OD750 improved by 24% under at 60 h). In addition, the salt tolerance of Syn2973 was further enhanced via overexpressing rate-limiting step of glycerol-3-phosphate dehydrogenase and down-regulating the gene rfbA encoding UDP glucose pyrophosphorylase. Together, the growth of end-point strain M-2522-GgpPS-drfbA was improved by 62% than the control strain M-pSI-pSII at 60 h under 0.5 M NaCl condition. Finally, a comparative metabolomic analysis between strains M-pSI-pSII and M-2522-GgpPS-drfbA was conducted to understand the carbon flux in the engineered M-2522-GgpPS-drfbA strain, and the results showed that more carbon flux was redirected from ADP-CLC to GG synthesis. The study provides important engineering strategies to improve salt tolerance and GG production in Syn2973 in the future.